Interpreting Islam - Donnan, Hastings (SAGE, 2002)
Surrounded by myths and stereotypes, Islam is one of the least understood religions in the West. Interpreting Islam provides a penetrating guide to the diversity and richness of contemporary knowledge about Islam and Muslim society in general.
Keywords: Islam.; Islamic countries -- Social life and customs.; Islam; Pays musulmans -- Mœurs et coutumes.; RELIGION -- Islam -- General.; Manners and customs; Islamic countries